Distraction : a mind that went out to play [D:AMTWOTP] - Li, Huiyuan (2015)
This research project entitled D:AMTWOTP presents a range of playful and light-hearted distractions that fits into a fictional workstation. Through diverging user’s attention to seemingly mindless activities, the project intervenes the tendency to constantly seek after a desired outcome (objective). This project hopes to trigger user’s curiosity as a form of motivation through this intervention. Ultimately, it questions existing negative connotation of the word “distraction”, and invites users to rethink their expectation of “distraction”. D:AMTWOTP stands for, “Distraction: A Mind That Went Out To Play.”